The Geochemistry of the Alluvial Topaz associated with the Jurassic kwandonkaya Granites in North-East Jos, Nigeria. - Ajayi, Abiola Olanrewaju (Obafemi Awolowo University, 2014)
Occurrences of topaz, associated with cassiterite mineralization within the Jurassic younger granite complex in Nigeria has been mentioned by several authors. This project reports the result of an integrated study of the geology, geochemistry, mineralogy and petrogenetic setting of the alluvial topaz found occurring within the kwandonkaya younger granite complex.